Implementation of Tariqah Dhikr in Strengthening the Character of Tahfidz Santri in Al-Qur'an Al-Falah Islamic Boarding Schools and Suryalaya Islamic Boarding Schools - Boy Arief Rochman; Ulfiah; Achmad Mudrikah; Supyan Sauri (Yayasan Azka Hafidz Maulana, 2022)
Tarekat/thoriqoh has the meaning of the way, (either charity, muroqobah, wirid, dhikr, and so on). The practice that is emphasized in this tarekat is dhikr which is done using jahr dhikr (obvious) and khafi dhikr (silent, hidden). The teachings of this tarekat are followed by tahfidz students. This teaching is practiced in religious and social life, aiming to shape behavioral changes in thoriqoh congregations, in order to increase religious obedience in establishing relationships with Allah SWT and humans, as well as changing one's personality to be better and have noble character. The study in this study was to determine the implementation of Dhikr Tariqah in Strengthening the Character of Tahfidz Santri in Al-Qur'an Al-Falah Islamic Boarding Schools and Suryalaya Islamic Boarding Schools who adhered to the Naqsyabandiyah Order at Islamic Boarding Schools. This research is a type of descriptive qualitative research. In collecting data, researchers used sources from subjects and objects. As for the data collection techniques, namely using Observation, Interview and Documentation. Based on research foundIt has been going well with the moral indicators of the students getting used to carrying out dhikr activities on time. This is inseparable from the implementation of Dhikr Tariqah in strengthening the character of students in Islamic boarding schools, the process of forming in behavioral changes that are carried out on santri congregations so that they can become better individuals in terms of character/behavior and in their lives. However, if it is associated with the various theories used in the Dhikr theory and character strengthening theory, it has been implemented effectively and optimally. Changes in behavior formed by the congregation are also very diverse, such as being on the path of goodness, having a wiser attitude, being patient, sincere and always prioritizing the afterlife.